2012
DOI: 10.3109/14767058.2012.666114
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of preterm labour via the modulation of inflammatory pathways

Abstract: Pregnancy is characterized by a complex interplay of inflammatory events regulated by both the innate and acquired immune systems. Similarly, parturition can be viewed as the activation of "pro-labour" inflammatory pathways, which drive cervical ripening and myometrial activation. Premature activation of these pathways, for example, by infection, can lead to preterm labour and birth. Nuclear factor κβ is a key modulator of these pathways and functions by regulating the expression of prostaglandins, chemokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…Numerous pathways culminate in preterm birth, including infection and/or inflammation (MacIntyre et al, 2012). The development of therapeutics to manage and prevent preterm labour can only arise from a complete understanding of the role of inflammation in initiating uterine contractions and membrane rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pathways culminate in preterm birth, including infection and/or inflammation (MacIntyre et al, 2012). The development of therapeutics to manage and prevent preterm labour can only arise from a complete understanding of the role of inflammation in initiating uterine contractions and membrane rupture.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 An increasing body of evidence supports the involvement of inflammation also, in the absence of overt infection, in preterm birth. 2 A key mediator of the inflammatory response in gestational tissues at the time of labor is NF-k light chain enhancer of activated B cells (NF-kB); however, data have also implicated activator protein 1 (AP-1) and CCAAT/enhancer-binding proteins (C/EBPs) in the regulation of inflammatory pathways associated with the onset of labor. 6e9 In various animal models of preterm labor (PTL), the Gram-negative bacterial cell wall component, lipopolysaccharide (LPS), is administered systemically to mimic bacterial infection during pregnancy or locally via an intrauterine injection to reflect ascending vaginal infection and/or chorioamnionitis.…”
mentioning
confidence: 99%
“…Evidence from both human and animal studies indicates that activation of inflammatory pathways in gestational tissues is a shared mechanism common to both normal and preterm birth. 2,3 Intrauterine inflammation is also associated with fetal brain injury, which may lead to longterm neurological disorders, such as cerebral palsy. 4,5 An increasing body of evidence supports the involvement of inflammation also, in the absence of overt infection, in preterm birth.…”
mentioning
confidence: 99%
“…It has also been indicated that maternal diet affects microbes identified at the important maternal-fetal interface of the placenta (85,86). Both preeclampsia and preterm delivery are conditions characterised by disturbed inflammatory responses (87,88). Hence the mechanism for the beneficial effects of certain diets on the risk of preeclampsia and preterm delivery may be through reduced inflammation due to intake of vegetables (24,30,32) and probiotic food (26,29).…”
Section: Possible Explanations For Findings and Comparison With Othermentioning
confidence: 99%